Exploring Service Quality Measurement in a Higher Education Setting: A Bibliometric Study - Kristiani Nira Wijayanti; Panggih Raharjo Alim; Iys Syabilla Rusda; Dian Ratna Sawitri (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
Higher education, as an educational institution, has a vital role in improving the quality of service its staff provides to give satisfaction and create a better educational experience for students. This study uses a bibliometric method to analyze the existing literature on measuring service quality in higher education with the aims of: 1) identifying the past and forecast future research trends service quality measurement in higher education, and 2) analyzing the patterns of collaboration between authors, institutions, and countries in publications related to measuring service quality in higher education. The research used a literature study with a bibliometric approach using VOSViewer and Microsoft Excel. The database used is SCOPUS. The results show that over three decades (1995-2025), there have been fluctuations in the number of publications. Three hundred ninety-nine articles were written by 159 researchers affiliated with 160 institutions in 80 countries, covering 25 subject areas. The themes are 1) Educational Service Quality, 2) Educational Research Methodology, 3) Educational Service Quality Assessment, and 4) Educational Service Quality Satisfaction. A comprehensive explanation of the findings and future direction is discussed in the paper.